Text mining techniques for healthcare provider quality determination : methods for rank comparisons - Cerrito, Patricia B. (Hershey, PA : Medical Information Science Reference, 2010)
"This book discusses defining a patient severity index for risk adjustments and comparison of patient outcomes to assess quality factors"--Provided by publisher.
1. Introduction to ranking models -- 2. Data visualization and data summary -- 3. Statistical methods -- 4. Predictive modeling versus regression -- 5. The charlson comorbidity index -- 6. The all patient refined diagnosis related group -- 7. Risk adjustment based upon resource utilization -- 8. Text mining and patient severity clusters -- 9. Working from claims data -- 10. Use of risk adjustment models for provider reimbursements -- 11. How to check measures for adequacy
Includes bibliographical references and index
Keywords: Data mining; Medical car -- Evaluation; Outcome assessment (Medical care)